2022
DOI: 10.1177/20503121221118992
|View full text |Cite
|
Sign up to set email alerts
|

Global impact and contributing factors in varicose vein disease development

Abstract: Varicose veins are convoluted, expanded, and stretched subcutaneous veins of the lower leg and are the most frequently reported medical condition. This condition has a higher prevalence in Western and developed countries. Inadequacy of the valves results in reflux of blood in the veins of the lower leg. The present study aims to describe the epidemiology and contributing factors (risk factors and pathological factors) in the development of varicose veins disease. PubMed/Medline, Science Direct, Google Scholar,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 81 publications
0
15
0
1
Order By: Relevance
“…This patho-physiology phenomenon makes the prolonged occupational standing a recognized risk factor for chronic venous disease (CVD). 1,2 According to a 12 year Danish prospective study, occupational prolonged standing in healthy subjects was a risk factor for CVD, with a relative risk of 1.75 (95% CI 0.92 to 3.34) for men and 1.82 (95% CI 1.12 to 2.95) for women. 3 The data were in-line with a Scandinavian investigation reporting a risk ratio for varicose veins of 1.85 for men and 2.63 for women, with results adjusted for age, social group, and smoking habits.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…This patho-physiology phenomenon makes the prolonged occupational standing a recognized risk factor for chronic venous disease (CVD). 1,2 According to a 12 year Danish prospective study, occupational prolonged standing in healthy subjects was a risk factor for CVD, with a relative risk of 1.75 (95% CI 0.92 to 3.34) for men and 1.82 (95% CI 1.12 to 2.95) for women. 3 The data were in-line with a Scandinavian investigation reporting a risk ratio for varicose veins of 1.85 for men and 2.63 for women, with results adjusted for age, social group, and smoking habits.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…While the exact cause of VVs remains unclear, several exacerbating factors have been identified. Common risk factors include increasing age, being female, pregnancy, smoking, a family history of venous diseases, and being overweight [8][9][10][11]. Prolonged periods of standing at work significantly increase the likelihood of VV development and serve as a significant occupational risk factor [11].…”
Section: Introductionmentioning
confidence: 99%
“…Common risk factors include increasing age, being female, pregnancy, smoking, a family history of venous diseases, and being overweight [8][9][10][11]. Prolonged periods of standing at work significantly increase the likelihood of VV development and serve as a significant occupational risk factor [11]. Genetics, the deterioration of elastic tissue, and venous thrombosis within the venous wall are just a few factors that can lead to valve weakening and dysfunction [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Varicose veins is a common vascular disease in developed countries. ( 1 ) The disease is characterized by clearly visible, dilated, tortuous, and possibly prominent subcutaneous veins in the lower extremities. ( 2 ) Previous studies using self-reported questionnaires have estimated the prevalence of VVs at 31 and 32%, respectively.…”
Section: Introductionmentioning
confidence: 99%